Estimating risk of word-finding problems in adults undergoing epilepsy surgery. (29th November 2016) - Busch, Robyn M.; Floden, Darlene P.; Prayson, Brigid; Chapin, Jessica S.; Kim, Kevin H.; Ferguson, Lisa; Bingaman, William; Najm, Imad M.
Abstract : Objective: This retrospective, observational study examined the frequency and magnitude of change in naming ability as a function of side/site of epilepsy surgery and identified predictive factors to assist clinicians in identifying patients at low, moderate, or high risk of postoperative naming decline. Methods: A total of 875 adults with pharmacoresistant epilepsy (454 left/421 right; 763 temporal/87 frontal/25 posterior quadrant) met inclusion criteria and completed the Boston Naming Test before and after surgery. Clinically meaningful change in naming ability was assessed using reliable change indices for epilepsy. Demographic, cognitive, and seizure variables were examined to determine factors most predictive of naming decline and to develop a decision tree to assist with clinical decision-making. Results: Naming decline was rare in right-sided resections and did not exceed the level expected by chance (5% overall; 90% confidence interval [CI] ± 2%). Naming decline occurred in 41% (CI ± 5%) of patients after left temporal resection (TLR) compared to 10%–12% (CI ± 10%–19%) in other left-sided surgical groups. A sizable proportion of left TLR patients (17%; CI ± 4%) showed substantial declines in naming (>11 points). Decline following left TLR was related to later age at seizure onset, older age at surgery, and higher preoperative naming ability. These factors correctly predicted naming decline in 68% of patients and were associated with degree of decline following left TLR. A decision tree is provided to assist clinicians in identifying patients at low, moderate, or high risk for postoperative naming declines. Conclusions: In addition to discussions regarding risk for memory decline following left TLR, patients should be counseled about potential decline in word-finding ability.